Clinical Profile and Outcomes of Severe Acute Maternal Morbidities in a Tertiary Care Centre, Bangalore, India: A Descriptive Study - Sushma Yalagandula; Ravi N Patil; C Sathyavani (JCDR Research and Publications Pvt. Ltd., 2024)
Introduction: Many complications can occur during pregnancy, delivery, and the immediate post-partum period that necessitate admission to the Intensive Care Unit (ICU). As maternal mortality is declining in many areas of the developing world, studying it alone may not be sufficient to provide information on the quality of care given. Therefore, the emphasis is more on Severe Acute Maternal Morbidity (SAMM) or Maternal Near Miss (MNM), which has emerged as a promising alternative to maternal mortality reviews. This approach has an advantage over maternal mortality as it draws attention to the reproductive health of surviving women. Aim: To determine the clinical profile, predisposing clinical conditions, and outcomes of SAMM. Materials and Methods: A descriptive study was conducted at Bangalore Baptist Hospital, Bangalore, Karnataka, India, from November 2020 to June 2022. Data were collected on all pregnant women and postpartum women up to 42 days after delivery who were admitted to the high-risk labour room, High Dependency Unit (HDU), and ICU. A total of 191 patients were enrolled, and various variables were studied, including demographic details, gestational age, co-morbidities, intensive care management, and neonatal outcomes. Women with Life-Threatening Conditions (WLTC), SAMM, and Maternal Deaths (MD) were noted, and using these parameters, the Severe Maternal Outcome Ratio (SMOR), MNM incidence ratio, and mortality index were calculated. Results: Among the 191 women with life-threatening conditions, 187 had SAMM, and four patients succumbed to death. The majority of SAMM cases were due to obstetric haemorrhage, observed in 73 patients (46.2%). This was followed by hypertensive disorders in pregnancy, seen in 65 patients (41.1%), and sepsis, seen in 15 patients (15.24%). The SMOR was calculated to be 44.05%. The MNM ratio was 43.13%, and the MNM mortality ratio was 46.75:1. A mortality index of 20.94% was reported in the study. Out of 155 births, 128 were live births, 14 were intrauterine deaths, 10 were fresh still-births, and three were early neonatal deaths. Conclusion: Screening for high-risk pregnancies and timely detection of severe maternal morbidity are important steps toward promoting safe obstetric care. A multi-disciplinary team with good ICU care and availability of blood and blood products will help decrease maternal mortality.